Sistem Informasi Dalam Perencanaan Pembangunan Daerah Pada Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Brebes - Suyudi Suyudi (Media Aplikom, 2010)
This research entitled : "Management System Information for Region Development Planning at The Office of Region Development Planning (Bappeda) of Brebes Regency” . This research was aimed to describe application of management information system in development planning of Brebes Regency was conducted in Bappeda of Brebes Regency. This research was conducted in Bappeda of Brebes Regency as leading sector in development planning. Research’s target is apparatus of Bappeda of Brebes Regency. Research method used qualitative method, sampling method used purposive technique, data collecting method used in depth interview, observation and documentation. Data analyzed technique used interactive model analysis. Result of research showed that development planning process Bappeda of Brebes Regency done by convergence of top down and bottom up mechanism. Top down planning done through data synchronization about development planning program which released by central government through passing Propenas and province government through Province Propeda. For a while, bottom up mechanism done by data collected by SKPD, result of Musrenbang, public aspiration. Through top down and bottom up mechanism so the development planning earn as according to public aspiration and or local real needed and the other side do not oppose against the development program which have been marked by vertical government. Application of information system in compilation development planning in Bappeda of Brebes Regency done by computer using as main peripheral functioned to process the input and data processing. But, the computer exploiting not yet been supported with a special software designed for the activity of development planning. Process of the input and processing still be done manually program by using Microsoft Excell Program.